2019
DOI: 10.3389/fnhum.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Disorientation: Clinical and Theoretical Significance of Long-Lasting Improvements Following Imagery-Based Training

Abstract: Neuropsychological studies on acquired topographical disorientation have provided useful insights into the contribution of different brain regions to human navigation. However, little is known about the possibility to restore navigational skills after brain damage. Here we describe the case of No Longer Lost (NLL), a 49-year-old man who complained of severe topographical disorientation following traumatic brain injury. Extensive neuropsychological evaluation at baseline revealed selective episodic memory defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Despite the sluggishness of the fMRI response relative to the speed of neuronal firing, this work nevertheless showed that these category-selective reactivation patterns during recall were detectable during the recall period and several seconds before the participants verbalised the recalled event -consistent with the idea that category-selective reinstatement in visual cortex is cuing the memory-system to retrieve remembered items (Polyn et al, 2005). Moreover, others have found that mental imagery of scenes and faces can be decoded from PPA and FFA, and in ventral OTC generally, suggesting that the activity in these areas during memory recall carries stimulusspecific visual information (Boccia et al 2019;Reddy et at., 2010). But are category-selective areas representing fine-grained detail regarding the recalled stimulus, or are they merely representing the category?…”
Section: Reactivation Of Perceptual and Mnemonic Representationssupporting
confidence: 76%
“…Despite the sluggishness of the fMRI response relative to the speed of neuronal firing, this work nevertheless showed that these category-selective reactivation patterns during recall were detectable during the recall period and several seconds before the participants verbalised the recalled event -consistent with the idea that category-selective reinstatement in visual cortex is cuing the memory-system to retrieve remembered items (Polyn et al, 2005). Moreover, others have found that mental imagery of scenes and faces can be decoded from PPA and FFA, and in ventral OTC generally, suggesting that the activity in these areas during memory recall carries stimulusspecific visual information (Boccia et al 2019;Reddy et at., 2010). But are category-selective areas representing fine-grained detail regarding the recalled stimulus, or are they merely representing the category?…”
Section: Reactivation Of Perceptual and Mnemonic Representationssupporting
confidence: 76%
“…For example, individuals with episodic memory deficits, such as patients with dementia and schizophrenia (Tromp et al, 2015;Kanchanatawan et al, 2018;Das et al, 2019), might benefit from a training of their primal navigational system as an indirect way of boosting their episodic memory system. In particular, a recent single-case report on a patient suffering from topographical disorientation has demonstrated the positive effect on episodic memory of an imagery-based navigational training (Boccia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, few recent studies have reported improvements in declarative memory performance following a navigational training in clinical populations. A single-case study on a patient suffering from topographical disorientation, for example, has described a secondary positive effect of an imagery-based navigational training on episodic memory (Boccia et al, 2019). At the group level, instead, an improvement of long-term memory capabilities (recognition memory) has been observed in older individuals following a training program on a way nding game in virtual reality (Wais et al, 2021).…”
Section: Discussionmentioning
confidence: 99%